Illocutionary Acts Performed by Anna in Frozen II - Vinesya Yuslia Fatma; Hanna Sundari (JEdu: Journal of English Education, 2021)
The research aims to identify the illocutionary act performed by Anna the secondary character in Frozen II. The research design of this paper is a qualitative framework in content analysis method. The unit of analysis was 218 utterances as illocutionary acts from the movie script. The utterances then were analysed and categorized into types of illoctionary acts. According to the result of the research, there are four types of illocutionary acts in the script, there are; 60 representatives utterances, 54 directives utterances, 5 commisives utterances, and 100 expressive utterances. Meanwhile, declarative utterance was not found